Pásztori múzsa a nagyvárosban - Gellérfi, Gergő (Antikvitás & Reneszánsz, 2018)
The title of my paper refers to a remark of Charles Witke, who specifies Juvenal’s Satire 3 in his monograph of Latin Satire as the eclogue of the urban poor. The interlocutor (who is also the main speaker in this case) of the satire says farewell to a friend before leaving his home for good, just like Meliboeus in Vergil’s First Eclogue. Both dialogues take place in natural environment, so to say, in a locus amoenus, however the setting of the satire is somewhat different from the traditional bucolic scenes. In my paper, I present the aforementioned bucolic features of the beginning and closure of Satire 3, after a brief summary of the other Juvenalian Satires showing the influence of bucolic poetry.